DISTRIBUSI DAN KOMPOSISI JENIS IKAN DEMERSAL YANG TERTANGKAP TRAWL PADA MUSIM BARAT DIPERAIRAN UTARA JAWA TENGAH [Fish distribution and composition demersal fish caught by trawl in west season in north waters of Central Java] - Tri Ernawati (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2007)
Research on demersal fish resources using research vessel Bawal Putih was carried out during the West monsoon (December, 2005) in the northern waters of Central Java. Sampling was done by trawl net with swept - area method and was pulled by speed of 3 knots. The maximum time of towing trawl at every station was 1 hour. The stations were 30 in number with 20 - 50 m in depth. The catch rate distribution of demersal fish between 2.16 - 234.08 kg/hour and the average was 61.6 kg/hour. The fish composition consists of 37 families and 79 species. The dominant families were Leiognathidae (38.9 %), Synodontidae (10.75%), Nemipteridae (10.65%) and Mullidae (8.76%). While the dominant species were Leiognathus splendens (25.3%), Upeneus sulphureus (8.4%), Leiognathus decorus (7.07%), Nemipterus japonicus (6.7%) and Saurida longimanus (4.2%).